C-Reactive Protein Binds to Cholesterol Crystals and Co-Localizes with the Terminal Complement Complex in Human Atherosclerotic Plaques - Pilely, Katrine; Fumagalli, Stefano; Rosbjerg, Anne; Genster, Ninette; Skjoedt, Mikkel-Ole; Perego, Carlo; Ferrante, Angela M. R.; De Simoni, Maria-Grazia; Garred, Peter (Frontiers in Immunology, 2017)
Inflammation is a part of the initial process leading to atherosclerosis and cholesterol crystals (CC), found in atherosclerotic plaques, are known to induce complement activation. The pentraxins C-reactive protein (CRP), long pentraxin 3 (PTX3) and serum amyloid P component (SAP) are serum proteins associated with increased risk of cardiovascular events and these proteins have been shown to interact with the complement system. Whether the pentraxins binds to CC and mediate downstream complement dependent inflammatory processes remains unknown. Binding of CRP, PTX3 and SAP to CC was investigated in vitro by flow cytometry and fluorescence microscopy. CRP, PTX3 and SAP bound to CC in a concentration-dependent manner. CRP and PTX3 interacted with the complement pattern recognition molecule C1q on CC by increasing the binding of both purified C1q and C1q in plasma. However, CRP was the strongest mediator of C1q binding and also the pentraxin that most potently elevated C1q mediated complement activation. In a phagocytic assay using whole blood we confirmed that phagocytosis of CC is complement-dependent and initiated by C1q-mediated activation. The pathophysiological relevance of the in vitro observations was examined in vivo in human atherosclerotic plaques. CRP, PTX3 and SAP were all found in atherosclerotic plaques and were located mainly in the cholesterol-rich necrotic core, but co-localization with the terminal C5b-9 complement complex was only found for CRP. In conclusion, this study identifies CRP as a strong C1q recruiter and complement facilitator on CC, which may be highly relevant for the development of atherosclerosis.